Flexural behavior of composite beam with ferrocement permanent formwork. - Abdul Kadir, Mohammad Razali; Che Muda, Zakaria; Abang Ali, Abang Abdullah (1991)
This paper reports the flexural behavior of sixteen simply supported concrete ferrocement composite beams of span 2.342 m. The load transfer between the upright channel shape ferrocement formwork and the r.c core beam is achieved through t2 mm rectangular hump shear connectors. The formwork provides support for the fresh concrete during the construction stage and strength in the hardened state. 'The specimens were subjected to two point loading and the ultimate load,flexural behavior and failure mode were recorded. The results show that the composite beam with ferrocement formwork fail by flexural mode rather than shear bond failure. In general,it is found that the composite beam with shear connectors carried about 12 % higher load and 10% reserved flexural strength. The ferrocement formwork with and without shear connectors contributed about 21%-75% and 16%-50% respectively to the flexural strength of the composite beams.